Peran Modal Sosial dalam Pemberdayaan Masyarakat Nelayan Desa Bangsring pada Objek Ekowisata Bangsring Underwater Kabupaten Banyuwangi - Uma Adi Kusuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research exists based on economic problem that occurred in fishing communities at Bangsring Village. The problem is the marine haul has decreased significantly caused by damaged of the underwater ecosystem. Based on the theory of social capital by Brata (2004) on Syahyuti (2008), the role of social capital could direct to solve local economic development problems like poverty reduction. This research aim to know the process of empowerment that happens in Bangsring Village and the benefit. This research use qualitative method with phenomenology approach. This research found that social capital could become the solution to solve the problem that occurred in fishing communities at Bangsring Village by empowerment program. The empowerment program that run b y the fishing communities at Bangsring Village succeed to create the new economic potential through tourism sector. The existence of BUNDER (Bangsring Underwater) tourism object has become a blessing for the fisheries communities and the villager who live around that tourism object.Keywords: social capital, empowerment, ecotourism, fishing communities.